Pengaruh Curing Time Terhadap Material Komposit Serat Kulit Jagung Sebagai Alternatif Bumper Mobil - Yudo, Eko; Adha, Adha; Subhan, Muhamad; Yuliyanto, Yuliyanto (Manutech : Jurnal Teknologi Manufaktur, 2023)
One source of natural fiber whose utilization still needs to be developed is fiber from corn husk which is cheap, abundant and environmentally friendly. The increasing production of corn plants causes an increase in corn husk waste which is also higher. Even though this corn husk has very strong fiber and can be used as a composite of natural fibers. Composites reinforced with natural fibers have excellent corrosion resistance properties, as well as lower production costs, are more abundant and are considered to be more environmentally friendly. The aim of the study was to determine the effect of soaking 7% NaOH for 1 hour, 2 hours and 3 hours and the effect of curing time at temperatures of 95°, 105° and 115° for 4 hours on the tensile strength of the corn husk fiber woven composite and to determine whether corn husk woven fiber composite can be applied as a car bumper manufacture. Making samples using the hand lay-up method. The analysis was performed using the factorial method. The highest results were found in the tensile test specimens using a variation of NaOH immersion time for 2 hours at a temperature of 95°C having a tensile test strength of 19.93 MPa. Meanwhile, the lowest tensile test strength value was 12.13 MPa using a variation of NaOH immersion time for 3 hours with a temperature of 115°C. Based on the standard for making car bumpers, the corn husk woven fiber composite can be applied as an alternative material for making car bumpers.